Implemetasi Numbered Heads Together Berbantuan Media Kartu Angka Bergambar Pada Mata Pelajaran Matematika Siswa Sekolah Dasar - Anita Nurgufriani; Nurul Uyun; Juryatina; Ady Saputra (Bima Journal of Elementary Education, 2023)
The purpose of this study was to find out which gave better performance between using the Numbered Heads Together model assisted by number cards and picture media and Numbered Heads Together without media. The type of research used was quasi-experimental research, where respondents were grouped into two groups, namely the Numbered Heads Together group with media and the Numbered Heads Together group without media. The population in this study were all elementary school students in SDN Inpres Pela. The sampling technique was carried out by means of stratified cluster random sampling. The independent variable in this study is the learning media assisted learning model, while the dependent variable is mathematics learning achievement. The data collection methods used in this study were: 1) the documentation method, in the form of midterm exam scores, 2) the test, in the form of 25 multiple choice questions. Data analysis techniques in this study were: 1) balance test: using the t-test with the prerequisite test for normality test with the Lilliefors method and homogeneity test with the Bartllet test, 2) hypothesis testing: using the t-test. All analyzes of this study used a significance level of 5%. The conclusion of this study is that learning achievement in mathematics using the Numbered Heads Together model assisted by number cards and picture media is better than using the Numbered Heads Together model without media.